2015
DOI: 10.1123/ijspp.2014-0002
|View full text |Cite
|
Sign up to set email alerts
|

Time–Motion Analysis of a 2-Hour Surfing Training Session

Abstract: The results demonstrate that a 2-h surfing training session is performed at a lower intensity than competitive heats. This is likely due to the onset of fatigue and a pacing strategy used by participants. Furthermore, surfing training sessions do not appear to appropriately condition surfers for competitive events. As a result, coaches working with surfing athletes should consider altering training sessions to incorporate repeated-effort sprint paddling to more effectively physically prepare surfers for compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 7 publications
5
36
0
4
Order By: Relevance
“…The data of this study revealed that the paddling was the most practiced activity in surf (58%), as already observed in other studies [1,6,9,10], however, the great percentage of this movement was short duration (up to 5 seconds) and the longest paddling movement (between 61 and 180 seconds) had a small percentage, suggesting an activity with intercalary movements involving anaerobic metabolism, where the resynthesize of ATP is done through chemical reactions that do not require the presence of oxygen [11]. The data from the study by Mendez-Villanueva et al [1] verified that most of the intervals of the paddling corresponded to a longer period (between 11 and 20 seconds), but the proximate intervals more executed were done up to 10 seconds.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The data of this study revealed that the paddling was the most practiced activity in surf (58%), as already observed in other studies [1,6,9,10], however, the great percentage of this movement was short duration (up to 5 seconds) and the longest paddling movement (between 61 and 180 seconds) had a small percentage, suggesting an activity with intercalary movements involving anaerobic metabolism, where the resynthesize of ATP is done through chemical reactions that do not require the presence of oxygen [11]. The data from the study by Mendez-Villanueva et al [1] verified that most of the intervals of the paddling corresponded to a longer period (between 11 and 20 seconds), but the proximate intervals more executed were done up to 10 seconds.…”
Section: Discussionsupporting
confidence: 74%
“…To date there have been only two previous studies investigating the time-motion analysis of surfers during competition [1,6], and one study that investigated during training surf [9], and more one study in recreation surf [10]. Since the conditions of surfing are also dependent on the geographical location, it is important to carry out a timemotion analysis in the Portuguese surfers, since there is no study carried out in Portugal, and international studies are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the total stimulus of high ground reaction forces on bone is limited to only 1.8 min (i.e., 3.0%) while surfing, hence the positive bone remodeling potential of surfing would be significantly low. Secomb, Sheppard, and Dascombe (2014) recently supported these findings and reported surfers were riding waves only 2.5% of a 2 hr surfing session.…”
supporting
confidence: 73%
“…Aunque, para la mejora del entrenamiento técnico, se recomienda hacer sesiones en Investigaciones recientes sugieren que durante las dos eliminatorias competitivas y durante el entrenamiento los surfistas pasan el 50% del tiempo total remando en el agua, un 40% estáticos, esperando la mejor ola, un 5% navegando en olas, y un 5% remando para llegar a la rompiente para colocarse de la mejor manera para la siguiente ola (Secomb et al, 2015).…”
Section: Psicológicounclassified
“…Esta propulsión se produce a través de remar, usar equilibrio dinámico y la potencia del tren inferior para permanecer en el paipo y realizar maniobras (Secomb, Sheppard, & Dascombe, 2015) La planificación de un entrenamiento para esta disciplina deportiva depende de numerosos factores, y por ello se deben buscar unas bases científicas que aseguren un entrenamiento equilibrado (Gorostiaga, 2000).…”
unclassified